Mitochondria as therapeutic targets in acute kidney injury. Issue 4 (July 2016) - Hall, Andrew M.; Schuh, Claus D.
Abstract : Purpose of review: Mitochondria are complex intracellular organelles with a variety of important functions. The kidney tubule is densely packed with mitochondria, and mitochondrial dysfunction is thought to be central to the pathogenesis of acute kidney injury (AKI). Mitochondria therefore represent potential targets for novel therapeutic interventions in AKI. Recent findings: Several mitochondrial targeted approaches have shown promise in recent preclinical studies of AKI, including measures to: reduce oxidative stress within mitochondria; prevent mitochondrial fission and activation of cell death pathways; enhance recycling of damaged mitochondria via autophagy and mitophagy; and accelerate mitochondrial biogenesis postinsult. Summary: Recent studies show that it is now eminently feasible to pharmacologically manipulate various key aspects of mitochondrial biology in the kidney, and this has much potential for the future treatment of AKI. However, significant hurdles will have to be overcome in the translational pathway for these strategies to successfully migrate to the clinic.